2014
DOI: 10.1177/0267658313510926
|View full text |Cite
|
Sign up to set email alerts
|

Lexical encoding of L2 tones: The role of L1 stress, pitch accent and intonation

Abstract: Native language prosodic structure is known to modulate the processing of non-native suprasegmental information. It has been shown that native speakers of French, a language without lexical stress, have difficulties storing non-native stress contrasts. We investigated whether the ability to store lexical tone (as in Mandarin Chinese) also depends on the first language (L1) prosodic structure and, if so, how. We tested participants from a stress language (German), a language without word stress (French), a lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 74 publications
2
50
0
Order By: Relevance
“…The first F0 pattern that differentiated Chinese speakers from speakers of non-tonal languages is that Chinese speakers obtained significantly higher facilitation scores in F0 mismatches, suggesting that, in comparison with the control condition, Chinese speakers detected F0 variation faster than speakers of non-tonal languages. Higher facilitation scores and faster reaction times in F0 mismatches have also been obtained in lexical decision tasks in tonal languages (e.g., Yip, 2001) and in training studies with word-object pairs (e.g., Braun et al, 2014). For example, Braun et al (2014) showed that Chinese speakers were more accurate and faster at detecting F0 mismatches than speakers of German, Russian and French, suggesting a finer perception of F0 by speakers of tonal languages.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The first F0 pattern that differentiated Chinese speakers from speakers of non-tonal languages is that Chinese speakers obtained significantly higher facilitation scores in F0 mismatches, suggesting that, in comparison with the control condition, Chinese speakers detected F0 variation faster than speakers of non-tonal languages. Higher facilitation scores and faster reaction times in F0 mismatches have also been obtained in lexical decision tasks in tonal languages (e.g., Yip, 2001) and in training studies with word-object pairs (e.g., Braun et al, 2014). For example, Braun et al (2014) showed that Chinese speakers were more accurate and faster at detecting F0 mismatches than speakers of German, Russian and French, suggesting a finer perception of F0 by speakers of tonal languages.…”
Section: Discussionmentioning
confidence: 72%
“…For example, Lee and Nusbaum (1993) showed that Chinese speakers perceived segments and tones integrally in both a tone task and a flat pitch task whereas English speakers perceived them integrally only in the tone task. Likewise, identification and discrimination studies using word-level stimuli provide further evidence for different levels of integration (e.g., Braun & Johnson, 2011; Braun et al, 2014). In an AXB task, Braun and Johnson (2011) found that speakers of non-tonal languages could not ignore F0 in incongruent trials, albeit speakers of tonal languages used the F0 dimension more often – i.e., 7.1% by Dutch speakers versus 43% by Mandarin speakers.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although English is not considered as a tonal language, it is nonetheless characterized by a large range of pitch dynamics akin to tonal languages (Duanmu, 2004). By contrast, French exhibits less variability in pitch (F0) at the utterance level and is classified as a non-tonal and non-stress language at the word level (Braun et al, 2014;Vaissière, 1991). Moreover, pitch carries segmental information in American English while it does not in French, which could explain the subcortical strengthening of this stimulus feature in American listeners independently of whether the stimulus belongs to their native language or not.…”
Section: Effect Of Language Expertise On F0 Representationmentioning
confidence: 99%
“…Interestingly, in a cross-language experiment, Braun et al (2014) tested whether the complexity of the pitch system in the native language modulates encoding of non-native tonal speech sounds. In this experiment, native speakers of a non-stress language (French), after learning associations between pictures and non-words distinguished only by their tonal contrasts, exhibited more difficulties remembering these associations than native speakers of a stress language (German).…”
Section: Effect Of Language Expertise On F0 Representationmentioning
confidence: 99%
“…In contrast to Mandarin, languages like English do not have lexical tones; this means that tonal information at the syllable level does not contribute to lexical identity in English. Native speakers of English who learn Mandarin after the offset of the so-called 'critical period' for language acquisition (e.g., Lenneberg, 1967) thus find it difficult to use lexical tones in the recognition of spoken Mandarin words (e.g., Braun, Galts, & Kabak, 2014;Sun, 2012).…”
Section: Introductionmentioning
confidence: 99%